Diagnostic challenges posed by a rare alpha globin chain variant Hb Fontainebleau in a pregnant female and its potential effects in her children in view of multiple globin gene defects in her husband - Kainaz Sidhwa; Manisha Ramani Daruwalla; Ravikiran Pawar; Anita Nadkarni; Priya Hariharan; Pallavi Mehta; Amar Das Gupta (Wolters Kluwer Medknow Publications, 2019)
Alpha globin chain variants per se do not cause severe morbidity and mortality but can modify - usually ameliorate - the clinical manifestations of beta globin chain variants when co-inherited with the latter. They also pose challenges in interpretation of high-performance liquid chromatography histograms and require molecular analysis for proper characterization. Hemoglobin (Hb) Fontainebleau is a rare alpha globin chain variant [alpha 21(B2) Ala→Pro], of which only three families have been reported from India in the past. Here, we describe a case of Hb fontainebleau detected in heterozygous condition in a 19-year-old primigravida. Her husband was found to have a double heterozygous state for HbQ India and beta-thalassemia trait. This opens up the possibility of multiple combinations of hemoglobinopathies in the offspring.